Determining the Efficacy of a Novel Epstein - Barr Virus (EBV) Peptide Vaccine: A Rabbit Model Approach - J. Rajcáni; K. Szenthe; F. Bánáti; B. Ásványi; L. Stipkovits; S. Szathmary (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
The present study aimed to investigate the Use of Rabbit Model for Efficacy of a Novel Epstein-Barr virus (EBV) Peptide Vaccine. Epstein–Barr virus (EBV or human herpesvirus 4) causes infectious mononucleosis and is latent in most adults. EBV is commonly transmitted by infected saliva (hence the nickname the kissing disease). The Epstein-Barr virus (Human herpes virus 4) encodes about 80 proteins, 15 of which have at least 90 antigenic epitopes. When many of the immunogenic EBV proteins stimulate T cell receptors (TCR), but few interact with B cell receptors (BCR), immunization was found to protect against them. B cell activation and subsequent antibody production have been linked to at least three envelope glycoproteins (primarily gp350/220), latency associated membrane proteins (LMPs), and EBNA3/C. The EBV vaccines designed so far fall into two categories: those preventing any kind of infection (can be used for prophylaxis of EBV-associated malignancies) and those designed for therapeutic purposes (to be used in subjects already infected).The preventive vaccines protecting against acute disease (such as IM) contain, as a rule, the gp350/220 polypeptide (s) encoded by the BLLF1 gene. In contrast, vaccines destined for tumor prevention rather consist of peptides derived from latency associated nuclear proteins (EBNA 2, 3 and 6) and/or from the oncogenic latent membrane proteins (LMP1/LMP2A). The advantage of the peptide vaccine presented here is the low probability of the induction of autoimmune responses, such as the ASIA syndrome, which may occur in a proportion of immunized patients.